Revolusi Pemikiran: Memahami Peran Pendidikan dalam Menghadapi Era Teknologi 5.0 - Peea, Febriano; Anneke, Djoys Rantung; Naibaho, Lamhot (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This article discusses how education can act as a fundamental pillar in shaping human thinking to face the complex challenges that arise along with technological advances. Education not only guides individuals in spiritual, moral and ethical aspects, but also plays a central role in shaping human paradigms regarding technological innovation. Teachers' ability to use technology is also a form of readiness to face the technological era 5.0. The aim of this research is to describe the role of education in facing the technology era 5.0. The research method used in this research is literature study. The findings of this research indicate that the integration of technology in educational teaching can increase student engagement and help them develop a deep understanding of religious values. The revolution in thinking in the context of understanding the role of education in facing the Technology Era 5.0 reflects the need for transformation in the education system to answer the challenges and opportunities that arise along with technological advances. In this era, education is not only considered as a conveyor of information, but also as a catalyst for developing 21st century skills such as creativity, critical thinking, and collaboration. Education must be able to produce individuals who are not only skilled in using technology, but also able to adapt and innovate in the face of rapid change. This Thought Revolution also emphasizes the importance of inclusion and accessibility of education amidst the even development of technology.